Ageism and Behavior Change During a Health Pandemic: A Preregistered Study - Vale, Michael T.; Stanley, Jennifer Tehan; Houston, Michelle L.; Villalba, Anthony A.; Turner, Jennifer R. (Frontiers in Psychology, 2020)
The COVID-19 pandemic has led to a suspected surge of ageism in America and has imposed critical health and safety behavior modifications for people of all ages (Ayalon et al., 2020; Lichtenstein, 2020). Given that older adults are a high-risk group, maintaining their safety has been paramount in implementing preventive measures (i.e., more handwashing, social distancing); however, making such behavior modifications might be contingent on how one views older adults (i.e., ageist stereotypes). Therefore, the goal of the current pre-registered study was to explore if hostile and benevolent ageism relate to pandemic-related fear and behavior change. An online survey assessing responses to the pandemic was taken by 164 younger and 171 older adults. Higher hostile ageism predicted lower pandemic-related behavior modification. Those high in benevolent ageism reported lower behavior change, but also reported higher pandemic-related fear; however, when pandemic-related fear was considered a mediator between the two, the directionality between benevolent ageism and behavior change switched, indicating a suppression effect. These findings highlight that ageist attitudes do predict responses to the pandemic and that hostile and benevolent ageism are distinct facets that have unique implications during a health pandemic.